Police Culture and the Management of Crime Victims in Wakari LGA, Taraba State, Nigeria - Rosemary Onchi Daniel; Gani Joshu; Geoffrey Nanbal Shipurut (International Journal of Education, Management, and Technology, 2026)
The management of crime victims is a critical indicator of policing effectiveness and the performance of the criminal justice system, yet in Wukari Local Government Area (LGA) of Taraba State, Nigeria, an enforcement-centred police culture marked by delayed responses, extortion, and procedural inefficiencies has raised serious concerns about victims’ protection and welfare. This study examines the influence of police culture on the management of crime victims in Wukari LGA, identifies prevalent forms of victimization, and evaluates how institutional practices shape victims’ experiences. Guided by Restorative Justice Theory, a descriptive cross-sectional survey design was employed, drawing a sample of 400 respondents from a projected population of 374,800 using Taro Yamane’s formula. Data were collected through structured questionnaires and supplemented with interviews involving ten key informants, and were analyzed using descriptive statistics and thematic evaluation. The findings reveal that prevailing police culture in Wukari significantly undermines victim management, with widespread extortion, delayed crime scene response, slow investigations, and manipulation of evidence contributing to secondary victimization. As a result, victims frequently feel neglected and lose confidence in law enforcement, which in turn fuels underreporting of crimes. The study concludes that the management of crime victims in Wukari LGA is largely ineffective due to entrenched policing norms and institutional deficiencies, and recommends the adoption of victim-centred policing, enhanced officer capacity and training, and strengthened accountability and oversight mechanisms to improve victim protection and restore public trust.